2006
DOI: 10.1016/j.ccr.2005.12.013
|View full text |Cite
|
Sign up to set email alerts
|

p63 mediates survival in squamous cell carcinoma by suppression of p73-dependent apoptosis

Abstract: We demonstrate that deltaNp63alpha is an essential survival factor in head and neck squamous cell carcinoma (HNSCC) through its ability to suppress p73-dependent apoptosis. Inhibition of endogenous p63 expression by RNAi induces apoptosis selectively in HNSCC cells that overexpress deltaNp63alpha. Knockdown of p63 induces the proapoptotic bcl-2 family members Puma and Noxa, and both their induction and subsequent cell death are p53 independent but require transactivating isoforms of p73. Inhibition of p73-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
506
4
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 401 publications
(545 citation statements)
references
References 57 publications
(90 reference statements)
34
506
4
1
Order By: Relevance
“…Direct interaction between p63 and p73 has also been reported in HNSCCs. 8 This tumor type often shows a high expression level of ΔNp63α that inhibits the tumor-suppressor function of TAp73. Our analysis of the potential mechanism of this inhibition, however, suggests that most of it is probably due to promoter squelching although the formation of hetero-complexes between transactivating p73 isoforms and inactive p63 isoforms on promoter sites with a reduced number of TA domains may contribute as well.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Direct interaction between p63 and p73 has also been reported in HNSCCs. 8 This tumor type often shows a high expression level of ΔNp63α that inhibits the tumor-suppressor function of TAp73. Our analysis of the potential mechanism of this inhibition, however, suggests that most of it is probably due to promoter squelching although the formation of hetero-complexes between transactivating p73 isoforms and inactive p63 isoforms on promoter sites with a reduced number of TA domains may contribute as well.…”
Section: Discussionmentioning
confidence: 99%
“…We used this specific combination as it has been shown that direct interaction between these two isoforms inhibits the tumor-suppressor activity of TAp73β in HNSCC cells. 8 Introduction of the homotetramer mutations (E370K, K377E, E380R and R397E) in ΔNp63α led to a marked decrease in co-IP efficiency with TAp73β, indicating that hetero-tetramer formation was repressed by these mutations also in a cellular context ( Figure 5). Interaction between the hetero-tetramer mutants of TAp73β (E363K) and of ΔNp63α (E377E) again showed a strong co-IP efficiency in all tested combinations.…”
Section: Hetnoe Experiments Of the Complex (Supplementary Figures S3hmentioning
confidence: 99%
See 2 more Smart Citations
“…If this were the case then one would have to take into account the fact that DN p63/p73 proteins can have pro-proliferative and possibly oncogenic activity. In fact, DNp63, like some p53 mutants, promotes the survival of squamous cell carcinoma (SCC) by blocking the TAp73 pathway (Rocco et al, 2006). In addition, many SCC cells express both mutant p53 and DNp63 (Hibi et al, 2000).…”
Section: Mutant P53 and P63/p73: What Lies Ahead?mentioning
confidence: 99%